Aplicación de la espirometría con broncodilatador adrenérgico en el diagnóstico del EPOC en pacientes de 60 a 85 años que acuden al centro de Salud Enrique Ponce Luque de la ciudad de Babahoyo, periodo diciembre 2022 – mayo 2023 - Cerezo Botto, María Mercedes (2023)
In the research work entitled Application of spirometry with adrenergic bronchodilator in the diagnosis of COPD in patients between 60 and 85 years of age who attend the Enrrique Ponce Luque health center in the city of Babahoyo, period December 2022 – May 2023, the main objective is to determine the reference spirometric values in the application of spirometry with adrenergic bronchodilator in the diagnosis of COPD in patients from 60 to 85 years of age who attend the Enrique Ponce Luque health center in the city of Babahoyo the methodology used focuses on being an analytical, deductive, Quali-Quantitative study Retrospective, since the information will be obtained from medical records where the reaction that occurred when applying spirometry with an adrenergic bronchodilator in the diagnosis of COPD will be observed, concluding that the use of spirometry becomes an important tool and thanks to it has been possible to classify respiratory diseases, so it has been identified It was found that 70% belong to the obstructive group, 9% to the mixed group, and 13% to the restrictive pattern.